2017
DOI: 10.1038/s41598-017-08537-2
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-mediated SOD-2 upregulation contributes to epithelial-mesenchymal transition and migration of tumor cells in aflatoxin G1-induced lung adenocarcinoma

Abstract: Tumor-associated inflammation plays a critical role in facilitating tumor growth, invasion and metastasis. Our previous study showed Aflatoxin G1 (AFG1) could induce lung adenocarcinoma in mice. Chronic lung inflammation associated with superoxide dismutase (SOD)-2 upregulation was found in the lung carcinogenesis. However, it is unclear whether tumor-associated inflammation mediates SOD-2 to contribute to cell invasion in AFG1-induced lung adenocarcinoma. Here, we found increased SOD-2 expression associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 33 publications
(53 reference statements)
1
27
0
Order By: Relevance
“…Tumor-associated inflammation also participates in the regulation of EMT, which contributes to cancer invasion and metastasis. Yi et al (34) recently reported that SOD may favor inflammation-mediated EMT and migration of tumor cells in AFG1-induced lung adenocarcinoma. We have previously reported that SOD-dependent production of ROS promoted the invasion of pancreatic cancer cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated inflammation also participates in the regulation of EMT, which contributes to cancer invasion and metastasis. Yi et al (34) recently reported that SOD may favor inflammation-mediated EMT and migration of tumor cells in AFG1-induced lung adenocarcinoma. We have previously reported that SOD-dependent production of ROS promoted the invasion of pancreatic cancer cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…However, in various solid tumors, because antioxidant mechanisms are activated at higher levels than in normal cells, tumor cells can be more tolerant to excessive ROS levels than normal cells [77]. NRF2-dependent antioxidant enzymes such as SOD, glutathione peroxidase (GPX), glutathione reductase (GSR), peroxiredoxin (PRX), and thioredoxin reductase (TXNRD) are upregulated in tumor cells, and high expression of these proteins is associated with poor prognosis in tumor patients (Table 1) [78][79][80][81][82][83]. Mitochondrial SOD2 was shown to be highly expressed in ovarian cancer patients and contribute to antitumor therapy resistance [84].…”
Section: Mtor-dependent Antioxidant Mechanism In Solidmentioning
confidence: 99%
“…The reports related to the relationship between E-cadherin and MSCs are limited to epithelial-mesenchymal transition (EMT) of stem cells. SOD2 is involved in the earlier stage of transition of E-cadherin-to-N-cadherin during EMT of stem cells [33]. Given the requirement of mitochondrial superoxide at the onset of EMT, SOD2 may inhibit EMT in epithelial cells by suppressing mitochondrial ROS.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, SOD2 has roles in protection against cell death, oxidative stress, ionizing radiation, and inflammatory cytokines [31,32]. Mitochondrial SOD2 regulates epithelial-mesenchymal transition and, as a result, the downregulation of E-cadherin, an epithelial marker, in SOD2 knockdown cells is partly inhibited [33]. Additionally, an E-cadherin increase in spheroid formation is proposed to be a key factor that elicits the formation of the spheroid and promotes therapeutic potency of the proliferative and paracrine activity seen in UCB-derived MSCs [29].In this study, we propose that our 3D spheroid MSC culture system, containing aggregated cells tightly adhering to each other, can maintain intracellular functions that are similar to physiological conditions in vivo.…”
mentioning
confidence: 99%